Risk And Return Model of Digital Cryptocurrency Asset Investment In Indonesia - Rico Nur Ilham; Isfenti Sadalia; Nisrul Irawati; Irada Sinta (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
Cryptocurrency is an investment commodity that can generate returns and already has a license to be traded in exchange trading through the Indonesian Commodity Futures Trading Regulatory Agency (BAPEPTI). There are quite a lot of crypto digital assets traded in Indonesia through the trading company Indodax. The purpose of this research is focused on formulating a risk management process in cryptocurrency digital asset investment. In addition, from the results of this study, a policy recommendation known as LCTR or